External electrical stimulation of cardiomyocytes to achieve synchrony at physiological frequencies. - Muhammad Parasuram. (2012)
Induced pluripotent stem cell colonies have the capability of differentiating into beating clusters of embryoid bodies (EBs). Being patient-derived, these represent a source of autologous cardiomyocytes for cardiac cell therapy. However, limited clinical success has been achieved due to 1) low cardiomyogenic efficiency; 2) sub-physiological contraction rates; and 3) unsynchronized contractions among beating clusters. To address these issues, the effects of external electrical stimulation on cardiomyogenic efficiency and contracting behaviors of EBs were studied. Electrical stimulation has been shown to be implicated in embryonic cardiomyogenesis, and hence was applied to developing EBs. Results show that cardiomyogenesis in developing EBs was not enhanced with electrical stimulation. On the other hand, developed embryoid bodies with spontaneous contractions displayed very good response to external electrical stimulation at optimized parameters. It was shown that beating clusters with low contraction rates (0.1 Hz) could be electrically stimulated and trained to contract at near-physiological rates (0.75 Hz). Importantly, unsynchronized beating clusters could be trained by prolonged and stepwise electrical stimulation into rhythmic synchrony for extended periods of up to six hours before contraction rates decreased. Taken together, these results imply that optimized electrical stimulation can generate homogenously contracting EBs for the application in cardiac cell therapy.